Pattern of Co-infection with Dengue Fever: An Observational Study (Bangladesh Journal of Child Health, 2021)
Background: Dengue fever is a major public health problem in Bangladesh. Suspicion, attention, and early tests are necessary to identify concurrent illnesses with dengue. This study was assessed to find out the other infections associated with Dengue fever to minimize morbidity and mortality.Materials & Methods: Hospitalized patients with fever were initially selected. After clinical and laboratory evaluation, fever with dengue NS1 or IgM positive cases were included. Among the 175 dengue patients; during follow-up, some patients had a persistent high fever, cough, dysuria, appearance/deepening of jaundice,and other toxic features that could not correlate with dengue. Relevant investigations were done to find out the co-infections among them.Results: Co-infection was found in 13.1% cases, among 5to 13 years of age group with female predominance. Dengue NS1 was found positive in 39.1% and IgM positive in 60.9% of cases. Typhoid fever 39.1%, paratyphoid fever 4.3%, rickettsial fever 13%, HAV infection 26%, HEV infection 8.7%, UTI 4.3%, and bacterial pneumonia 4.3% were found among the cases of dengue fever as co-infection.Conclusion: The study shows that dengue patients are at a higher risk of having other infections. Thirteen percent of the dengue patients were found associated with different co-infection.Bangladesh J Child Health 2020; VOL 44 (3) :157-160